2014
DOI: 10.15376/biores.10.1.256-271
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Composite Films based on κ-carrageenan Reinforced by Cellulose Nanocrystal from Kenaf Fibers

Abstract: Through alkali treatment, bleaching, and sulfuric acid hydrolysis, cellulose nanocrystals (CNCs) were prepared from kenaf fibers and were used as reinforcement materials in biocomposites based on κ-carrageenan. Biocomposites in the form of films were prepared by solution casting of a mixture of κ-carrageenan, glycerol, and various amounts of CNCs (0 to 8 wt%). Fourier transform infrared spectroscopy (FTIR) revealed that alkali treatment followed by bleaching totally removed lignin and hemicellulose from the ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 38 publications
7
45
0
1
Order By: Relevance
“…Besides, when carrageenan concentration was increased to 80% and combined with high sorbitol content, the increasing N concentration resulted in increased EM values. S might absorb less water and hence the mobility of film samples was decreased, which then resulted in higher EM values due to the effectiveness of N. Zarina and Ahmad also reported that carrageenan films with up to 4% nanocellulose had higher EM values. On the other hand, increasing the proportion of glycerol in the plasticizer had a decreasing effect on EM for all carrageenan ratios.…”
Section: Resultssupporting
confidence: 88%
“…Besides, when carrageenan concentration was increased to 80% and combined with high sorbitol content, the increasing N concentration resulted in increased EM values. S might absorb less water and hence the mobility of film samples was decreased, which then resulted in higher EM values due to the effectiveness of N. Zarina and Ahmad also reported that carrageenan films with up to 4% nanocellulose had higher EM values. On the other hand, increasing the proportion of glycerol in the plasticizer had a decreasing effect on EM for all carrageenan ratios.…”
Section: Resultssupporting
confidence: 88%
“…Application: soft gel capsules Carrageenan/CMC/Acetic acid [103] The blend of kappa-carrageenan & cellulose derivatives exhibit good conductivity. Application: biopolymer electrolytes Carrageenan/NCC/Glycerol [104] Incorporation of NCC (up to 4%) shows good dispersion, superior mechanical properties & thermal stability of film. Application: packaging material Agar/MFC/Chitosan methylisothiazolinone crosslinking with TPP [105] Incorporation of MFC/C−MIT composite enhances film tensile property and excellent antimicrobial activity.…”
Section: Preparation Of Seaweed/cellulose Blendsmentioning
confidence: 99%
“…This finding indicated that good compatibility between the seaweed and the OPS nanofillers was achieved, in which the TS of the nanocomposite films were enhanced by the presence of OPS nanoparticles compared to the blank seaweed film. This phenomenon could be due to the high specific surface area and uniform dispersion of the nanoparticles in the matrix, and good bonding between the hydrophilic oil palm nanoparticles and seaweed with the presence of hydroxyl groups (-OH groups), which could provide better filler-matrix interfacial interactions and also allow for the effective transfer of stress through a shear mechanism from the matrix to the particles (Huq et al 2012;Khan et al 2012;Mohaiyiddin et al 2013;Zarina and Ahmad 2014;Rosamah et al 2016;Abdul Khalil et al 2016). Hence, it was believed that the nanocomposite film could sustain greater loads when up to 20% of OPS nanofillers were incorporated.…”
Section: Mechanical Properties Of Bio-nanocomposite Filmsmentioning
confidence: 99%